Pengukuran Speed dan Impedansi Akustik pada Tanah Liat dengan Memanfaatkan Sinyal Echo Ultrasonik - Lusiana Lusiana; Agus Indra Gunawan; Bima Sena Bayu Dewantara (Jurnal Rekayasa Elektrika, 2019)
Each material has its own characteristics, which are represented by the value of speed/ultrasonic wave propagation speed (C) and acoustic impedance/material resistance (Ztl). One technique that can be used to obtain these characteristics is by applying ultrasonic testing. This technique utilizes two ultrasonic sensors as transmitter (UST) and receiver (USR) to get signal properties from each material. The measurement mechanism is nondestructive testing (NDT) where the material tested is not damaged so it does not change the character of the sample. In this research, material characteristics are represented by reflected signals from material (echo). To process the echo signal data and get the characteristics of the sample, we need a number of data processing algorithms such as Fast Fourier Transform (FFT), Peak Detection, and Grid Search. By processing echo from reflected signals, C and Ztl values can be obtained. From the experimental results obtained, the values of C and Ztl in sample 1 with a density of 1856.97573 g/m3 are C = 636 m/s and Ztl = 474640 Ns/m3, samples 2 with a density of 1792.94208 g/m3 of C = 491 m/s and Ztl = 408080 Ns/m3, while the sample 3 with a density of 1663.85025 g/m3 is C = 434 m/s and Ztl = 405639 Ns/m3. The value of material characterization shown that a dense clay also has higher C and Ztl.